1982
DOI: 10.1542/peds.70.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Early Scintigraphic Diagnosis of Bone Stress and Fractures in Athletic Adolescents

Abstract: A study of radionuclide bone scintigraphy in adolescents was conducted to evaluate the pattern of stress-related abnormalities and their correlation with both symptoms and roentgenography. In 26 episodes of stress-related abnormal scintigraphy, 12 (46%) had a multifocal pattern of abnormalities. Forty foci were identified by scintigraphy, with 11 (28%) exhibiting abnormal roentgenograms. These multiple abnormalities were frequently unsuspected clinically, and studies limited to symptomatic areas would have fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addition, it was found that the longer the symptoms of spondylolysis were present, the greater the likelihood to need surgery to treat this condition [1, 2]. For early diagnosis of spondylolysis, it has been recommended to perform a SPECT scintigraphy as soon as stress‐related symptoms do appear in young soccer players with normal plain radiographs [13, 15, 21]. Particularly, SPECT scintigraphy has been recommended over planar bone scintigraphy because the former has a higher sensitivity to detect spondylolysis and improves accuracy of anatomic localization of the defect [3, 22].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was found that the longer the symptoms of spondylolysis were present, the greater the likelihood to need surgery to treat this condition [1, 2]. For early diagnosis of spondylolysis, it has been recommended to perform a SPECT scintigraphy as soon as stress‐related symptoms do appear in young soccer players with normal plain radiographs [13, 15, 21]. Particularly, SPECT scintigraphy has been recommended over planar bone scintigraphy because the former has a higher sensitivity to detect spondylolysis and improves accuracy of anatomic localization of the defect [3, 22].…”
Section: Discussionmentioning
confidence: 99%